Sintesis Nanomaterial Mangan Oksida dengan Metode Bebas Pelarut - Nanda Saridewi; Syukri Arif; Admin Alif (Syarif Hidayatullah State Islamic University, 2015)
Manganese dioxide (MnO2) known as manganese oxide which has a variety polimorfi crystal structure, such as β-, α-, δ- and γ- MnO2. Each of manganese oxide material comprises a tunnel structure. With the structure of the tunnel which is owned by manganese oxide material is widely used as selective catalysts, ion exchange, and the exchange of molecules. Manganese oxide is synthesized using free methods solvent. Synthesis process is performed with a temperature variation of 90, 120, and 150 °C. The results was characterized by XRD and SEM. XRD diffraction patterns produced showed that the manganese oxide that is formed is a β-MnO2 (pyrolusite) with an optimum temperature of 120 °C. The resulting material also has a range of nanoparticles that reach 14:08 nm crystal size. Mangan shaped morphology produced oxide can degrade dye rhodamine B.DOI: http://dx.doi.org/10.15408/jkv.v0i0.3147.